Protocol for the isolation of silk glands from silkworms for snRNA-seq and spatial transcriptomics - Yan Ma; Keshu Dong; Jie Hu; Yiyun Tang; Hanfu Xu (STAR Protocols)
Summary: The silk glands (SGs) of silkworms specifically synthesize silk proteins, thus strongly influencing the yield and quality of silk. Here, we present a protocol for isolating SG nuclei from silkworms and obtaining high-quality tissue slices for spatial transcriptomics. We describe steps for rearing, dissecting, and nucleus isolation. We then detail procedures for embedding, frozen section, and RNA capturing and sequencing. This protocol enables the exploration of the spatial distribution of SG cells at single-cell resolution.For complete details on the use and execution of this protocol, please refer to Ma et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.